Employment Benefits on PT. Jamkrida Banten - Rasmin Rasmin (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this study was to find out how the practice of employee benefits at PT Jamkrida Banten. This research method uses literature study and field study. Researchers made direct observations on the object of research. The results showed that PT Jamkrida Banten is a regional company that complies with regulations including the application of accounting. PT Jamkrida Banten applies PSAK 24 regarding employee benefits. With the implementation of PSAK 24 at PT Jamkrida, the rights and obligations of employees and the company become clear.